Plastic Waste-Based Paving Blocks: Towards A Sustainable Circular Construction Material - Joey Limbongan; Risman Firman; Muhammad Ali Taufan (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2026)
This study introduces a method using layered plastic blending technology to combine three primary types of plastic waste (PET, PP, and LDPE) with sand. The objective is to analyze the effects of plastic-sand composition variations on the mechanical properties of paving blocks, including water absorption, compressive strength, and abrasion resistance. The research was conducted experimentally through a plastic melting and hot-mixing process with sand using four composition ratios: 100% plastic: 0% sand, 75% plastic: 25% sand, 50% plastic: 50% sand, and 25% plastic: 75% sand. Results indicate that the 75% plastic: 25% sand mixture has the highest compressive strength of 11.64 MPa. The 100% plastic: 0% sand mixture exhibited the lowest absorption (<3%) and the best abrasion resistance (<0.062 mm/min). Increasing sand content generally reduced mechanical performance due to the inadequate distribution of plastic in coating the aggregate particles. Overall, plastic waste-based paving blocks demonstrate strong potential as an alternative construction material. Nevertheless, long-term environmental durability testing is recommended to ensure their applicability under real field conditions.